Molecular Identification of Streptococcus equi subspecies equi in Horses: 1S. H. Mahmood@; 1Abd M.H. Al_Judi and 2Haidar Khalid Mosstafa - Mahmood, S. H. (The Iraqi Journal of Veterinary Medicine, 2014)
The objective of this study to evaluate the existence of Streptococcus equi subspecies equi as probable agents of naturally occurring infection of the equine upper respiratory disease from the Equestrian club in Baghdad city. Nasal swabs and pus samples from 141 horses with upper respiratory tract infections were collected. Results indicated that different microorganisms were isolated and identified S. equi subsp equi (30 isolates), S. equi subsp zooepidemicus (14 isolates), S. equisimilus (9 isolates), Enterococcus. fecalis (17 isolates), Pasteurella spp. (29 isolates), Staphylococcus spp. (25 isolates), Bacillus spp. (24 isolates), Pseudomonas spp.(16 isolates), and E. coli (21 isolates). All 30 isolates of S. equi was characterized by biochemical tests. For molecular identification of the subspecies S. equi one genomic region SeM was amplified.